Rekonstruksi Kewenangan Pemerintah Daerah dalam Pengendalian Eksploitasi Tambang Rakyat: Analisis Yuridis Pasca Tragedi Bolaang Mongondow - FaridI, Fahmi; Buwana, Sukma Auliya Nata; Rengganis, Tresnasuci Leofanny; Ramdhani, Fahmi Ali (Universitas Pahlawan Tuanku Tambusai, 2025)
This study analyzes the reconstruction of local government authority in controlling community mining exploitation through a normative legal approach with a focus on the analysis of mining and local government laws and regulations. The normative legal analysis method is used to examine the synchronization and harmonization between Law No. 4 of 2009 concerning Mineral and Coal Mining, Law No. 23 of 2014 concerning Regional Government, and its derivative regulations in the context of the division of authority between the central, provincial, and district/city governments. The analysis was conducted on aspects of licensing, supervision, and law enforcement in community mining activities which have so far experienced overlapping authority and weak coordination between levels of government. The results of the analysis show that the reconstruction of local government authority requires a clearer and more assertive redistribution in terms of granting permits, implementing supervision, and enforcing sanctions against violations in community mining exploitation. The weaknesses of the non-integrated licensing system, the lack of technical supervision capacity at the regional level, and the unclear vertical coordination mechanism are the main factors contributing to the mining tragedy. The necessary reconstruction includes strengthening the authority of districts/cities in terms of licensing and operational supervision, increasing provincial authority in technical coordination and standardization, and strengthening the role of the central government in setting safety standards and system audits. The implementation of this authority reconstruction must be supported by strengthening institutional capacity, integrated information systems, and clear accountability mechanisms to prevent similar tragedies from happening again in the future.